Emerging trend on international capital flows and global value chains reconstruction under post COVID-19: a review. Issue 3 (3rd July 2022) - Song, Chang; Zhuang, Yuhang; Liu, Ziwei; Zhang, Hongyuan; Ding, Yibing
Abstract: The global outbreak of the COVID-19 pandemic has slowed down international investment and trade, and partially disrupted the global supply chain. This paper provides an overview of the findings in 80 scholarly articles from recent years, comprehensively summarises and analyzes the research on international capital flows and global value chain（GVC）reconstruction, and deeply reveals the impact of COVID-19 on OFDI, the change of OFDI performance before and after the pandemic and factors that may accelerate GVC reconstruction in the future. We identify research gaps in a combination of OFDI and GVC reconstruction at both the macro and micro level and suggest several future research topics such as political risk and bilateral relations factors, the role of China in OFDI and GVC dynamics, network and OFDI performance, network characteristics of GVC reconstruction, OFDI and GVC reconstruction.